Мотивация учения математике: сущность, функции мотивов, приемы формирования - Sogomonian T. S. (Pedagogical excellence and pedagogical technologies, 2016)
this article describes the main stages of learning motivation in mathematics, selected functions of the motives presented some methods of formation of motivation of learning mathematics
Keywords: мотивация; мотив; потребность; motivation; motive; этапы мотивации; приемы формирования мотивации; функции мотивов; need; stages of motivation; methods of formation of motivation; functions of motives